Chapter 8 Ethics of Selective Restriction of Liberty in a Pandemic - Savulescu, Julian (Oxford University Press, 2023)
Liberty-restricting measures are basic measures in combatting any pandemic. But whose liberty should be restricted? One standard response in public health ethics is to appeal to the "least restrictive alternative" necessary to achieve a public health goal. The problem is that in practice, greater restriction of liberty can lead to greater control of the pandemic and save more lives, though with increasing burdens to others. Liberty restriction is thus a question of the distribution of benefitsbenefits benefits and burdens in a population, a question of distributive justice. In this chapter, I argue that in some pandemics, such as COVID-19, it may be a more proportionate restriction of liberty to restrict the liberty of certain groups, rather than the population as a whole. Two arguments were given in the COVID-19 pandemic for liberty restriction: (1) protection of the vulnerable; (2) protection of the health service. These These are, however, more fundamentally issues about distributive justice. I explore how several approaches to distributive justice can support the differential differential differentialdifferentialdifferential restriction of liberty. In addition, I argue that the commonly accepted justificationjustificationjustificationjustificationjustification justification justification justification for liberty restrictions (that liberty restrictions may be justifiedjustifiedjustifiedjustifiedjustified justified to prevent direct harm to others) - can be overly simplistic, as illustrated by the COVID-19 pandemic. I argue that where risk groups (such as the elderly in the COVID-19 pandemic) are more likely to utilise limited health resources, they pose an indirect threat to others during the pandemic that warrants coercion. I argue there should be a side-constraint on justice of non-maleficence.non-maleficence.non-maleficence. non-maleficence. non-maleficence. non-maleficence. This This requires that there is a limit to harm which can be imposed on individuals for others, best captured by a collective duty of easy rescue. For groups such as the young, vaccination or lockdown may not constitute an "easy rescue" of those at greatest risk. I address the issue of whether selective restriction of liberty constitutes unjust discrimination and I propose an algorithm for making decisions about selective restriction of liberty.